2015
DOI: 10.1016/j.hfc.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Interventional and Device-Based Autonomic Modulation in Heart Failure

Abstract: Abstract/SummaryHeart failure is an increasingly prevalent disease with high mortality and public health burden. It is associated with autonomic imbalance characterized by sympathetic hyperactivity and parasympathetic hypoactivity. Evolving novel interventional and device-based therapy has sought to restore autonomic balance by neuromodulation.Results of preclinical animal studies and early clinical trials have demonstrated its safety and efficacy in heart failure. In this review article, we will discuss speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 65 publications
0
4
0
2
Order By: Relevance
“…New nonpharmacologic treatments of heart failure have focused on increasing parasympathetic activity via the use of different stimulation approaches or sympathetic blockade with renal sympathetic denervation and left cardiac sympathectomy. 1,2 The preclinical results of these procedures are encouraging, but initial clinical trials have been unpredictable and harmful. [1][2][3] A preliminary study reported modest efficacy of left cardiac sympathetic denervation in patients with dilated cardiomyopathy, 4 and this procedure has been shown to modify favorably the incidence of life-threatening arrhythmia.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…New nonpharmacologic treatments of heart failure have focused on increasing parasympathetic activity via the use of different stimulation approaches or sympathetic blockade with renal sympathetic denervation and left cardiac sympathectomy. 1,2 The preclinical results of these procedures are encouraging, but initial clinical trials have been unpredictable and harmful. [1][2][3] A preliminary study reported modest efficacy of left cardiac sympathetic denervation in patients with dilated cardiomyopathy, 4 and this procedure has been shown to modify favorably the incidence of life-threatening arrhythmia.…”
Section: Perspectivementioning
confidence: 99%
“…1,2 The preclinical results of these procedures are encouraging, but initial clinical trials have been unpredictable and harmful. [1][2][3] A preliminary study reported modest efficacy of left cardiac sympathetic denervation in patients with dilated cardiomyopathy, 4 and this procedure has been shown to modify favorably the incidence of life-threatening arrhythmia. 5 Besides the decrease of sympathetic activity, several mechanisms of neuromodulation in these new interventional modalities probably contribute to their favorable effect, including reduced apoptosis, metalloproteinase inhibition, and augmentation of the anti-inflammatory effect of vagal activity.…”
Section: Perspectivementioning
confidence: 99%
“…9 Outro resultado destacado na pesquisa, apresentado em 4 trabalhos, foi o aumento da tolerância ao exercício no teste de caminhada de 6 minutos 22,25,26,29 . Ademais, os pacientes com IC submetidos à DSR apresentaram melhora do quadro clínico, como a redução de arritmias e de disfunções metabólicas, essa melhora do quadro clínico é relatada em pelo menos 8 trabalhos 8,10,19,20,21,24,28,34 .…”
Section: Resultsunclassified
“…In the last years, bipolar unselective vagal neuromodulation has been investigated for several indications like sepsis, autoimmune‐diseases, obesity, headaches, obsessive‐compulsive‐disorders, and depression . By influencing the—supposed to be dysfunctional—parasympathetic cardiac activity, neuromodulation techniques like VNS seem to have positive effects especially on heart failure and—preclinically investigated—on atrial fibrillation . Significant changes in BP during unselective VNS have not been reported.…”
Section: Discussionmentioning
confidence: 99%